KESIAPAN PENGEMBANGAN EKOWISATA BERBASIS MASYARAKAT DI DESA WONOREJO, KABUPATEN SITUBONDO, JAWA TIMUR - Mijiarto, Joko; Andrea, Garsione Agni; Gusriza, Fondina; Windiarti, Khofiatul Rosdiana (Fakultas Kehutanan Universitas Winaya Mukti, 2023)
Wonorejo Village is the first village in Situbondo Regency. However, since it was established that the tourist village visit was not as expected. This is because the determination of the top to bottom tourist village so that the community is not ready to continue the determination made. This study aims to assess the readiness of the community in the development of community-based ecotourism. Data were collected through literature study, observation and in-depth interviews with each stakeholder. The data were then analyzed into four categories, namely socio-economic, socio-cultural, environmental and management aspects. Based on the results of the analysis conducted, the community is good with a score 1.710 in the development of community-based ecotourism in Wonorejo Village. However, in some aspects it has value that still needs to be improved. Some things that can be taken into consideration in improving community readiness include increasing community involvement in management, sharing benefits, increasing the role of customs and conducting marketing promotions in order to increase the number of tourist visits.Â Keywords: community readiness; community-based ecotourism; wonorejo